Kepemimpinan Perempuan dalam Menjalankan Fungsi Keluarga pada Komunitas PEKKA (Perempuan Kepala Keluarga) - Ramadhany, Nurul (Al-Hukkam: Journal of Islamic Family Law, 2022)
The general headship of the family was that of a man (the husband) who was the family head, but now there began to be a shift in the role of the family head that was initially held by the male (the husband) shifted to that of the female (the wife). That reality can be seen from PEKKA communities in the village of rowoyoso, wonokerto district. It is different according to Islam. Islam views the man as the head of the family. The results of this study are expected to be helpful in the development of theories or sciences in the realm of islamic family law, particularly on the leadership of women in the family. This type of fieldwork with a qualitative approach is done on the PEKKA community. Data sources of primary data obtained by observation and interview techniques while secondary data sources are obtained by documentation techniques. Analysis techniques using interactive model and qualitative data analysis techniques from miles and hubermans. The study concluded that the concept of the family head is based on the women's community (PEKKA) of the village of rowoyoso that the family head does not have to be a man. Women may also become the family head despite the circumstances in their family. In Islam there is no restriction on women being the head of the family. The role of the PEKKA community (family head woman) in improving cooch